IMPLEMENTATION OF SPECIFIC TIME WORK AGREEMENT (PKWT) BASED ON LAW NO. 6 ANNUAL 2023 ABOUT CREATING WORK: TO WORKERS OF PT. EIGERINDO MPI REGIONAL SURABAYA - Dewi Mellyna Anggraeni; Wahjoeono, Dipo (COURT REVIEW: Jurnal Penelitian Hukum (e-ISSN: 2776-1916), 2025)
An uncontrolled increase in population can certainly result in higher needs for food, clothing and shelter. To be able fulfill these needs, humans must get work that can produce income so that all their needs for clothing, food and shelter can be met properly. The field of employment a everything that to related to the abor, both before the employment period, during the employment period and after the completion of the employment period. Getting a job and then working is one way for humans to fulfill their physiological needs. Every employee is obliged to the fulfill all employee the rights or a laborers in the Law of the Republic of Indonesia on number 6 (six) of 2023 (two thousand twenty three) law on Job Creation, but sometimes employers do not understand and comprehend the rights of workers or laborers that must be fulfilled. Before carrying out their duties as a laborer or worker, a work agreement will first be executed between PT. Eigerindo MPI with workers or employees to form a mutually bound working relationship. The work agreement should made in written form and shold obtain an agreement between the worker or laborer and the entrepreneur or what is known as the employer. The employment aggrement a prepared and provide by the company for workers, in this case PT. Eigerindo MPI, may take the form of either a fixed term the employment agreement (PKWT) or an indefinite a term employment aggrement (PKWTT). The implementation of the a fixed term in the employment agreement (PKWT) have must be based in the provisions in the applicable law and based on the principles of agreements which are generally stated in the Civil Code and specifically discussed in the law regarding employment, namely in Law Number 6 of 2023.